Proceedings of the Graduate Research in Education Seminar 2022 (GREduc 2022) - Faculty of Educational Studies (Faculty of Educational Studies, 2022)
The Graduate Research in Education Seminar (GREduc) 2022, held on 9 December 2022 and organized by the Faculty of Educational Studies, focused on the theme Improving Wellbeing and Resilience through Innovative Educational and Human Resource Research.